2015
DOI: 10.5489/cuaj.2435
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro cytocidal effect of water on bladder cancer cells: The potential role for intraperitoneal lavage during radical cystectomy

Abstract: Cytocidal effect of hypotonic shock can be achieved, to varying degrees, by exposing bladder cancer cells to water for at least 10 minutes. This in vitro study may have bearing on the effects seen with intraperitoneal lavage using sterile water during radical cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We have previously revealed cytocidal effects in bladder cancer cells [9,10]. However, the phenotypes were different in each bladder cancer cell line.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have previously revealed cytocidal effects in bladder cancer cells [9,10]. However, the phenotypes were different in each bladder cancer cell line.…”
Section: Discussionmentioning
confidence: 98%
“…Cell culture, observation of morphological changes, cell proliferation assay and cell membrane analysis were performed with reference to previous studies [9,10,15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While water is hypotonic, using it as irrigating uid during transurethral resection surgery is not ideal due to the risk of transurethral resection syndrome. However, continuous intravesical water irrigation immediately after the surgery can be a cheap but effective method in minimising the risk of tumour reimplantation [10][11][12] . A comparison between sterile water and MMC as irrigating agents in vivo after resection was done by Bijalwan et al Results showed that continuous bladder irrigation with sterile water after resection had comparable results to immediate intravesical MMC in terms of preventing tumor recurrence in NMIBC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Alternatively, several groups have utilized sterile water and saline irrigation over 18–24 h as a strategy to lyse floating tumors cells and prevent the re-implantation of cells into the bladder wall. [ 9 , 10 ] In our current study, we sought to evaluate continuous bladder irrigation with isotonic (0.9% NaCl) normal saline (CBSI) for two hours following TURBT as a strategy to reduce recurrence or progression in patients with NMIBC.…”
Section: Introductionmentioning
confidence: 99%